2021
DOI: 10.1136/bmjopen-2020-043525
|View full text |Cite|
|
Sign up to set email alerts
|

Mindfulness-based programmes to reduce stress and enhance well-being at work: a realist review

Abstract: ObjectivesTo understand how and why workplace mindfulness-based programmes (MBPs) work or do not work.DesignA realist review.Eligibility criteria for selectionWe considered any studies (experimental quasi-experimental, observational, qualitative and mixed-methods studies) of workplace MBPs as long as they provided data to explain our programme theories. All MBP formats and delivery modes were included.AnalysisConsistent with realist review methodology, we systematically screened and analysed data to explain ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 88 publications
(72 reference statements)
3
28
0
Order By: Relevance
“…Evidence from low, middle and high-income countries shows that school climate is important for positive student outcomes, including mental wellbeing, with feedback loops between teachers' improved mental wellbeing and pupils' (47-49). A realist review of MBIs at the workplace designed to improve employee welling found that the intervention triggered four mechanisms that participants were able to use: awareness/self-regulation, acceptance/compassion, feeling permitted to take care of the self, and a sense of growth and being able to attain goals (44). Critically, this research also found that a supportive environment at work was important, linking mindfulness practice to specific practice settings and existing goals and practices.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Evidence from low, middle and high-income countries shows that school climate is important for positive student outcomes, including mental wellbeing, with feedback loops between teachers' improved mental wellbeing and pupils' (47-49). A realist review of MBIs at the workplace designed to improve employee welling found that the intervention triggered four mechanisms that participants were able to use: awareness/self-regulation, acceptance/compassion, feeling permitted to take care of the self, and a sense of growth and being able to attain goals (44). Critically, this research also found that a supportive environment at work was important, linking mindfulness practice to specific practice settings and existing goals and practices.…”
Section: Introductionmentioning
confidence: 79%
“…Researchers' primary focus has been asking if mindfulness works rather than how and why it works (43). Most theories assume that practising mindfulness exercises bring about the observed changes (44) and that mindfulness is about changing the wiring of the brain and the psychology of individuals (39,42,44). A scoping review to elucidate the mediators, moderators and implementation factors in delivering universal mindfulness training in schools (45) identified mediators and moderators that influenced the outcome of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This is a real paradigm shift that involves both the individual and the organisation. More specifically, it is important that during the course of the intervention, professionals should feel safe in engaging in self-care at work and in sharing difficulties with colleagues [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, John Kabat-Zinn first developed a mindfulness-based stress reduction program, the Mindfulness-Based Stress Reduction Program (MBSR). Because of the increased interest in this program, programs based on MBSR were designed to cultivate mindfulness and integrate its practice into daily life [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%